Expressive Speech Acts of Taylor Swift in The Ellen Show - Salsabilla, Intan; Suraiya, Lucy (Program Studi Sastra Inggris, 2026)
This study analyzed Taylor Swift's expressive speech acts in The Ellen Show. This study aims to identify the categories of expressive speech and the adjectives manifested in the expressive speech acts to convey her emotions or feelings. The data were taken from three interview videos and analyzed using Ronan’s (2015) categories of expressive speech acts and Sinclair et al. (2017) for the types and functions of adjectives. This study employs a qualitative descriptive method. From a total of 62 data, seven categories of expressive speech were identified in Taylor Swift conversations with Ellen. They are agreement, disagreement, volition, thanking, non-directed complaints in exclamations, expressing sorrow, and greetings. The most frequently used category is agreement, with a percentage 29,04%. This reflects Taylor's humble, polite, and respectful personality. While qualitative adjectives are the most dominant type of adjectives used with a percentage of 65,71%. This shows that Taylor often conveys her personal feelings and experiences in new music promotion, her past viral moments, and personal revelations emotionally and deeply.